Influence of mechanical activation on curing processes of refractory concrete and its properties - Песчанская, Виктория Викторовна; Макарова, Анна Сергеевна; Голуб, Ирина Валериевна (Technology audit and production reserves, 2013)
Significant advantages of low-cement refractory concrete with low porosity, high mechanical strength, chemical resistance and thermal stability, and adaptability to the operating conditions in linings of thermal units determine the prospects for further increase in consumption of concrete and development of scientific bases of technology of its production. A promising method of creation of composite materials with an efficient structure and improved properties is the mechanical activation. We have studied the effect of the mechanical activation of electric corundum and a matrix component of low-cement corundum concrete on the change of the morphology and physical properties of materials, hardening kinetics and properties of the concrete. It was determined that an increase in the duration of the mechanical activation of electric corundum has a significant impact on the change of acid-base balance of suspensions, reactivity of the matrix component and the rate of hardening of a paste. The experimental research showed the possibility of use of the mechanical activation of components of the low-cement corundum concrete, as an effective way of directed control of activity of the matrix component, rate of cement hydration, formation of hydrogel and colloiding of cement phase, development of crystallization contacts between cement and aggregate particles that promote formation of an efficient structure and properties of refractory concrete.